고지방식이 마우스에서 금어초 추출물의 항당뇨와 항염증 효과 - 장미(Mi Jang); 박영희(Young-Hee Park); 황인국(In-Guk Hwang); 황병순(Byung-Soon Hwang); 김지영(Ji-Young Kim); 김기창(Gi-Chang Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2018)
본 연구에서는 고지방식이로 유도된 비만쥐 모델에서 금어초 추출물의 지질대사 개선, 혈당조절, 항염증 효과를 보고자 하였다. 이를 위해 C57BL/6 마우스에서 8주간 금어초 추출물을 경구투여 한 후 임상적 지표로 체중 변화, 장기 무게, 혈중 지질, 혈당, GTT, ITT, 염증 사이토카인, 염증 관련 단백질의 발현 정도를 조사하였다. 그 결과 금어초 추출물은 간, 복부피하지방의 무게를 효과적으로 감소시켰으며, 이는 고지방식이로 인한 비만 개선에 금어초 추출물이 긍정적인 영향을 미치는 것으로 판단된다. 또한 금어초 추출물의 투여는 혈중 중성지방과 총 콜레스테롤 그리고 간세포 손상으로 인한 AST 효소의 혈액 내 유출을 효과적으로 감소시켜 비만상태의 지질대사 이상과 간 손상을 최소화하는 것으로 생각된다. 또한 본 연구에서는 금어초 추출물의 비만으로 인한 혈당조절 장애 개선에 대한 효과를 알아보기 위하여 혈중 글루코오스와 인슐린 농도, 내당능, 인슐린 내성을 확인하였다. 그 결과 금어초 추출물은 유의적으로 혈중 글루코오스 농도를 감소시키고 인위적으로 투입된 글루코오스와 인슐린에 대해서도 혈당 조절 효과를 보였다. 그리고 금어초 추출물이 비만에서 나타나는 만성적인 염증상태에 대한 개선 효과를 알아보고자 하였다. 그 결과 금어초 추출물은 혈액 내 MCP-1, IL-6, IL-1β 등을 효과적 감소시켰으며 조직세포 내 iNOS, COX-2, TNF-α, IL-1β 발현 또한 억제하는 것으로 나타났다. 본 실험의 결과는 금어초 추출물이 비만상태에서 나타나는 고지혈증, 고혈당 그리고 과도한 염증반응을 감소시키고 억제하는 데 유의적인 효과가 있음을 보였다. 이와 같은 금어초의 생리활성은 비만에서 발생되는 각종 질병과 증상에 유익한 식의약소재로 활용 가능성을 보여준다. 더 나아가 이러한 식의약 소재 개발을 위해 심도 있는 반응 메커니즘 구명과 금어초 추출물에 함유되어 있는 기능성 물질 분리 및 동정에 관한 추가적인 연구가 필요할 것으로 판단된다. The objectives of this study were to determine and compare the anti-diabetic and anti-inflammatory effects of Antirrhinum majus L. extract (AME) in high fat diet-fed mice (HFD). C57BL/6 mice were assigned to five groups: ND (n=8; normal diet), HFD (n=8), and HFAME [HFD+100 mg/kg AME (n=10), HFD+300 mg/kg AME (n=8), and HFD+600 mg/kg AME (n=10) groups]. Mice were fed their assigned diets for 8 weeks. Mean body weight in the HFD group was 32% higher than in the ND group, but mean body weights in the HFAME groups were unchanged. Mean food efficiency ratio was higher in the HFD group than in ND controls, but significantly lower in HFD+600 mg/kg AME (n=10) groups than in the HFD group. Furthermore, liver, epididymal fat, and subcutaneous fat weights were lower in the HFAME groups than in the HFD group. In addition, mean plasma triglyceride and total cholesterol levels were significantly higher in the HFD group than in the ND group, and lower in the HFAME groups than in the HFD group. Similarly, mean fasting blood glucose was significantly lower in the HFAME groups than in the HFD group. The serum insulin and glucose concentrations were remarkably lower in the HFAME groups than in the HFD group. Insulin sensitivity was measured by glucose tolerance testing (GTT) and insulin tolerance testing (ITT) after animals had been on their respective diets for 6 weeks, and GTT and ITT results in the HFAME groups were significantly lower than in the HFD group. Furthermore, levels of inflammatory cytokines, that is, of monocyte chemoattractant protein-1, interleukin-6, and interleukin-1β, were lower in the HFAME than in the HFD group. In addition, AME prevented HFD-induced increases in the expressions of pro-inflammatory genes in liver, epididymal adipose tissue, subcutaneous fat. AME improved insulin resistance and exhibited anti-diabetic effects in HFD mice. Our findings suggest AME has potential utility for the prevention of nonalcoholic fatty liver disease. KCI Citation Count: 1